Accountability Practices in the History of Danish Primary Public Education from the 1660s to the Present - Christian Ydesen; Karen E. Andreasen (Arizona State University, 2014)
This paper focuses on primary education accountability as a concept and as an organizational practice in the history of Danish public education. Contemporary studies of education policy often address questions of accountability, but the manifestations of school accountability differ significantly between different national settings. Furthermore, accountability measures and practices have an impact on both the ways and means by which societies approach their educational systems. Hence there is a need to clarify the characteristics and traits connected with the concept. One way of approaching this endeavor is to turn to the history of education, because the discourse and practice of accountability incorporates numerous historical antecedents, technologies, and arguments. Based on primary as well as secondary sources this article presents the case of Denmark, analyzing the period from 1660 to the present. The article is analytically divided into four chapters, one treating the period of absolute monarchy, from 1660 to 1849; one treating the era of the nation state, from 1849 to 1933; one treating the welfare state, from 1933 to 1990; and one treating the era of globalization and the marketization of education, from 1990 to the present. The key analytical findings are that changing forms of government are reflected in accountability practices and accountability practices exert strong disciplining effects.